2018
DOI: 10.1038/s41598-018-25867-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel erythrocyte clumps revealed by an orphan gene Newtic1 in circulating blood and regenerating limbs of the adult newt

Abstract: The newt, a group of urodele amphibians, has outstanding ability to repeatedly regenerate various body parts, even in the terrestrial life-stage. In this animal, when the limb is amputated, a cell mass named the blastema appears on the stump and eventually gives rise to a new functional limb. Erythrocytes (red blood cells) in most non-mammalian vertebrates, including the newt, preserve their nucleus throughout their life-span, although physiological roles of such nucleated erythrocytes, other than oxygen deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…However, it was recently shown that circulating erythrocytes play an important role in limb regeneration by providing secretory molecules such as growth factors and matrix metalloproteases at the site of injury. 54 Whether circulating erythrocytes play a similar role during lens regeneration remains to be explored. Even though previous whole-mount fluorescent imaging demonstrated that the distribution of blood vessels between dorsal and ventral iris is similar, 55 OCT may allow us to quantify the dilation of the blood vessels and blood flow rates or oxygen saturation levels to uncover the function and contribution of these biological processes during dorsal iPEC transdifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was recently shown that circulating erythrocytes play an important role in limb regeneration by providing secretory molecules such as growth factors and matrix metalloproteases at the site of injury. 54 Whether circulating erythrocytes play a similar role during lens regeneration remains to be explored. Even though previous whole-mount fluorescent imaging demonstrated that the distribution of blood vessels between dorsal and ventral iris is similar, 55 OCT may allow us to quantify the dilation of the blood vessels and blood flow rates or oxygen saturation levels to uncover the function and contribution of these biological processes during dorsal iPEC transdifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The mesenchymal cells of the blastema originate from various tissues in the stump. During the formation of the blastema, severed nerves and blood capillaries at the stump also grow into the blastema [6,7]. The blastema establishes a three-dimensional axial pattern from which a patterned limb is eventually regenerated [2].…”
Section: Introductionmentioning
confidence: 99%
“…This ability of the newt to regrow organs is because of their ability to reprogram and dedifferentiate the terminally differentiated cells to trigger regeneration response ( Mehta and Singh, 2019a ). Such an exceptional regeneration ability of newts has been attributed to unique gene(s) that may have evolved from forming the regeneration tool box ( Bryant et al., 2017 ; Casco-Robles et al., 2018 ; Elewa et al., 2017 ; Evans et al., 2018 ; Keinath et al., 2015 ; Kumar et al., 2007 ; Matsunami et al., 2019 ; Mehta and Singh, 2019a ; Nowoshilow et al., 2018 ; Sanor et al., 2020 ; Smith et al., 2009 , 2019 ). Earlier, a newt gene Prod1, which encodes a transmembrane receptor, was found to be critical for maintaining proximodistal identity (pattern memory) during newt limb regeneration ( da Silva et al., 2002 ; Echeverri and Tanaka, 2005 ; Kumar et al., 2007 ; Mehta and Singh, 2019a ).…”
Section: Introductionmentioning
confidence: 99%